PENGARUH PEMBELAJARAN MODEL CONTEXTUAL TEACHING LEARNING BERBANTU MEDIA VIDEO TUTORIAL - Ayu Dewi Maghfiroh (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2017)
The purpose of this research is (1) to know whether there are differences of learning outcomes between students who get learning with Contextual Teaching Learning model Video Tutorial sub theme of Uniqueness of My Place of Study with learning outcomes that received learning by lecturing method, (2) Contextual Teaching Learning model Helpful Video Tutorials sub theme The uniqueness of the area where you can produce individual completeness and classical learning, and (3) how the students' motivation to the Contextual Teaching Learning model Video tutorial sub theme of the uniqueness of the area where you left me. The population is the students of SD Negeri Pandean Lamper 01. Samples taken using cluster random sampling technique, obtained class IV A experimental class and IV B control class. Data collection methods used include test methods and observation methods.